2007
DOI: 10.4067/s0717-95022007000100021
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Parameters and Sperm Morphology of Chinchilla Rabbit Fed With Different Planes of Soymeal

Abstract: The testicular parameters and sperm morphology were studied in twenty healthy Chinchilla breed bucks of rabbits fed with different planes of soybean meal. Their ages were between 6 to 10 months with their weights ranging from 1.4 to 1.9kg.The same quality of feeds was fed to each group throughout the study and at the rate of 0.5kg/head/day. The feeds contained graded percentage of soybean meal and growers mash.Semen used in this study was from the caudal epididymides while morphological aberrations were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 7 publications
2
14
2
Order By: Relevance
“…However, other measured testicular parameters were consistent with the report of Oyeyemi and Okediran (2007) but higher than the mean values reported by Oguike and Archibong (2011). These differences in testicular parameters could be due to breed differences, or variation in age of bucks (Oyeyemi and Okediran, 2007).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…However, other measured testicular parameters were consistent with the report of Oyeyemi and Okediran (2007) but higher than the mean values reported by Oguike and Archibong (2011). These differences in testicular parameters could be due to breed differences, or variation in age of bucks (Oyeyemi and Okediran, 2007).…”
Section: Resultssupporting
confidence: 73%
“…The mean testis weight recorded in this study was higher than 3.1 g reported by Franca et al (2002) but lower than 6.7 g reported by Herbert et al, (2005). However, other measured testicular parameters were consistent with the report of Oyeyemi and Okediran (2007) but higher than the mean values reported by Oguike and Archibong (2011). These differences in testicular parameters could be due to breed differences, or variation in age of bucks (Oyeyemi and Okediran, 2007).…”
Section: Resultscontrasting
confidence: 50%
“…It is now observed from this study that prolonged treatment of chloramphenicol will cause infertility when used at 25mg/kgbw for 20 to 25 days. This observation is similar to reports of Oyeyemi & Okediran (2007), Hughes & Varley (1980). The decrease noticed/observed as per the days of treatment in semen concentration indicated that prolonged treatment of chloramphenicol has adverse effect on fertility potential of the male animal.…”
Section: Discussionsupporting
confidence: 93%
“…The values were within the range of 6.00 to 16.00% reported by Ajayi (2009). The percentage of abnormal sperm cells in this study were below the upper limit of 20% recommended as the minimum for good reproductive potential and fertility in either normal mating or in artificial insemination (Oyeyemi and Okediran, 2007). The result of the visceral organ weights of male rabbits fed water spinach is presented in Table 4.…”
Section: Resultsmentioning
confidence: 95%